Mecanismos envolvidos nos efeitos do seleneto vinílico bis substituído (svbs) em modelos animais de depressão e de dor - Jesse, Cristiano Ricardo (2011)
The association between depression and chronic pain is frequent and bidirectional. The high number of patients with depression and chronic pain who are refractory to currently available drugs makes it important search for new drugs to treat these disease. The bis selenide is an organic selenium compound with activities such as antioxidant, antinociceptive and anti-inflammatory in mice. Thus, this study investigated the effect of bis selenide in models of depression and pain in mice, besides the pharmacological mechanisms involved. Oral administration of bis selenide (5mg/kg, p.o.) reduced the immobility time in tail suspension test (TST) with a maximal effect at 1 hour and it remained up to 6 hours in relation to control group. The effect caused by bis selenide in reducing the immobility time was observed at doses of 0.5, 1 and 5 mg/kg in the TST and the forced swimming test (FST) (article 1). The antidepressant-like activity of bis selenide was reversed by pretreatment with p-chlorophenylalanine ethyl ester (PCPA, an inhibitor of synthesis of serotonin), ketanserin (5-HT2A/2C receptor antagonist), ondansetron (5 -HT3 receptor antagonist) (article 1), L-arginine (an amino acid precursor of nitric oxide (NO)), sildenafil (phosphodiesterase inhibitor type 5, PDE-V), S-nitroso-N-acetyl-penicillamine (SNAP, an NO donor) (article 2), cromakalim (potassium channels - K+- opener), minoxidil (K+ channels opener) and GW 9662 (antagonist of peroxisome proliferator activated receptors gamma (PPARγ) (article 3). However, the antidepressant-like effect of SVBS (1 mg / kg, po) was not prevented by pretreatment with prazosin (α1-receptor antagonist), yohimbine (α2-receptor antagonist), propranolol (β-receptor antagonist), SCH 23390 (D1 receptor antagonist), sulpiride (D2 receptor antagonist) and WAY 100635 (selective antagonist of 5-HT1A) (article 1). Furthermore, when administered in a sub-active dose, the bis selenide (0.1 mg / kg, p.o.) showed a synergistic action with fluoxetine (an selective serotonin inhibitor reuptake), NG-nitro-L-arginine (an inhibitor of the NO synthase (NOS)), 7-nitroindazole (7-NI, a specific inhibitor of NOS neurornal), methylene blue (inhibitor of NOS and guanylate cyclase (GC)), 1H-1,2,4] oxadiazole [4, 3-a] quinoxaline-1-one (ODQ, a specific inhibitor of GC) (article 2), tetraethylammonium (TEA, a non-specific inhibitor of K(+) channels), glibenclamide (an ATP-sensitive K(+) channel inhibitor) charibdotoxin (a large and intermediate conductance calcium-activated K(+) channel inhibitor) and apamin (a small-conductance calcium-activated K(+) channel inhibitor) (article 3). The administration of bis selenide (0.1 5 mg/kg, p.o.) also did not modify the activity of monoamine oxidase A and B (MAO-A and MAO-B) and Na+K+ATPase in mice. The levels of nitrite/nitrate in the brain of mice were reduced by treatment of bis selenide (1 mg/kg). Treatment with bis selenide (1 and 5 mg/kg) decreased the depressive-like behavior and mechanical hypernociception in mice subjected to chronic constriction injury (CCI) (article 4). Moreover, the administration of bis selenide (5 and 10 mg/kg, po) showed a reduction in mechanical hyperalgesia and edema in inflammatory models induced by intraplantar (i.pl.) injection of Complete Freund Adjuvant (CFA), carrageenan (Cg) and prostaglandin E2 (PGE2) (article 5). The mechanical hyperalgesia induced by i.pl. injection of CFA or the brachial plexus avulsion (BPA) was attenuated by chronic administration of bis selenide without causing tolerance during treatment. Concomitant administration of bis selenide (5 and 10 mg/kg) with vincristine for 7 days attenuated the mechanical hyperalgesia from 3 to 28 days. According to this study, it may suggest that the mechanisms responsible for the antidepressant-like effect of bis selenide involve the modulation of serotonin (5-HT2A/C and 5-HT3) and PPARγ receptors and the NO/GMPc/K+ pathway. Furthermore, treatment with bis selenide reduced the depressive-like behavior induced by CCI and the mechanical hyperalgesia in inflammatory (CFA, Cg and PGE2) and neuropathic (BPA and vincristine) models. Thus, this study demonstrated that treatment with bis selenide showed antidepressant-like and anti- hyperalgesic effects in different models in mice.